2021
DOI: 10.3389/fmolb.2021.745649
|View full text |Cite
|
Sign up to set email alerts
|

Pan-Cancer Analysis of the Associations of TGFBI Expression With Prognosis and Immune Characteristics

Abstract: Transforming growth factor-beta-induced (TGFBI) protein has important roles in tumor growth, metastasis, and immunity. However, there is currently no pan-cancer evidence regarding TGFBI. In this study, we conducted a pan-cancer analysis of TGFBI mRNA and protein expression and prognoses of various cancer types using public databases. We also investigated the associations of TGFBI expression with tumor microenvironment (TME) components, immune cell infiltration, tumor mutational burden (TMB), and microsatellite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…At the same time, in the research conducted by the Yun Chen, TGFBI was also elevated in various kinds of cancers (cholangiocarcinoma, colon adenocarcinoma (COAD), esophageal carcinoma (ESCA), GBM, head and neck squamous cell carcinoma (HNSC), kidney renal clear cell carcinoma (KIRC), kidney renal papillary cell carcinoma (KIRP), liver hepatocellular carcinoma (LIHC), rectum adenocarcinoma (READ), stomach adenocarcinoma (STAD), and thyroid carcinoma), and it also showed a great value in the survival aspects. While for the clinical stage aspects, it was not very obvious for the KIRC [ 10 ]. In our results, although the OS and PFI show a strong correlation for the TMEM65, the predicting value of the gene for the clinical stage was more valuable for the early stage, especially for the BLCA and THCA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, in the research conducted by the Yun Chen, TGFBI was also elevated in various kinds of cancers (cholangiocarcinoma, colon adenocarcinoma (COAD), esophageal carcinoma (ESCA), GBM, head and neck squamous cell carcinoma (HNSC), kidney renal clear cell carcinoma (KIRC), kidney renal papillary cell carcinoma (KIRP), liver hepatocellular carcinoma (LIHC), rectum adenocarcinoma (READ), stomach adenocarcinoma (STAD), and thyroid carcinoma), and it also showed a great value in the survival aspects. While for the clinical stage aspects, it was not very obvious for the KIRC [ 10 ]. In our results, although the OS and PFI show a strong correlation for the TMEM65, the predicting value of the gene for the clinical stage was more valuable for the early stage, especially for the BLCA and THCA.…”
Section: Discussionmentioning
confidence: 99%
“…Although TMEM65 correlated with some unimportant immune-related genes, TMEM65 showed some indicative significance for the three markers for certain kinds of cancers, and the meaning behind it implies significant correlation with the prognosis of the immune therapy. At the same time, the three markers (TMB, MSI, and NEO) also attracted lots of attention in the recent similar explorations [ 10 , 11 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…In breast cancer, induction of EMT by overexpression of transcription factor SNAIL can render breast cancer cells resistant to the cytotoxic effect of CD8 + T cells through the induction of autophagy; and targeting an autophagy inducer (BECN1) restored CD8 + T mediated tumor cell lysis [ 62 ]. A recent pan cancer study indicated TGFBI as a prognostic marker in various cancers due to its involvement in various immune responses [ 63 ]. This is consistent with our analysis which showed a statistically significant positive association of infiltration of CD8 + T cells, CD4 + T cells, macrophages, neutrophils, and dendritic cells with TGFB1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…PPT models enabled the unbiased identification of gene programs relevant to tissue dynamics along tumor development, and allowed us to assemble an epithelial-intrinsic Immune Exclusion Signature (IES) defined by expression of DDR1, TGFBI, PAK4, and DPEP1. This aggregated signature is highly informative, as these genes have been implicated separately as immune modulators but not always in the context of CRC 26,91,92,71 . DDR1 has been reported to align collagen fibers in a way that excludes T cells from the breast TME 27 .…”
Section: Discussionmentioning
confidence: 99%